The Effect Of Immersion Time Variation in Polyvynyl Piprolidone Against Characteristics Of Scaffold Biocomposit Of Bacterial-Hydrocysiatatic Cellulose as Candidate - indrio, ludita (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
Bone defects due to trauma, tumors, congenital abnormalities, degeneration and other diseases are still major problems in the field of orthopedics and traumatology. Based on data in Asia, Indonesia is the country with the highest number of fracture sufferers, there are as many as 300-400 cases of bone surgery per month in hospitals. Dr. Soetomo Surabaya (Gunawarman et al, 2010). Repair of damaged bones can be overcome with material that can accelerate the process of bone healing (bone healing). This research was conducted to synthesize hydroxyaparite bacterial cellulose scaffold as a candidate for bone healing. Bacterial cellulose as a matrix was synthesized by culturing Acetobacter xylnum, while hydroxyapatite as filler was synthesized by immersion into a solution of CaCl2 and Na2HPO4, the scaffold formation process using freeze dried method. Composite formation was varied by immersion in Polyvynil pirrolidone (PVP) for 0, 1, 2, 3, 4 days. Furthermore, samples were characterized using FTIR-Spectroscopy showing the presence of carbonates containing apatite crystals in all five samples.